Integrasi Teori Belajar dan Nilai Islam Dalam Pendidikan Modern: Konvergensi Untuk Pembelajaran Efektif - Afifah, Siti Nur (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study aims to explore the application of learning theories within the perspective of Islamic teachings, emphasizing the convergence between religious values and modern teaching methods. In the current educational context, integrating religious approaches with contemporary learning strategies is increasingly important for building a moral and spiritual foundation in students. This research employs a qualitative methodology with an in-depth library research approach. The analyzed literature includes relevant journals, books, and official documents. The key findings reveal that Islamic teaching methods, such as hiwar (dialogue), qishah (stories), and amtsal (analogies), are effective in enhancing student understanding and engagement while reinforcing moral values. The implications of this study highlight the need for adaptation and implementation of Islamic teaching methods in modern educational contexts to create a more holistic and integrated approach. This research also opens opportunities for further studies focusing on the development of curriculum based on religious values that are relevant and effective in addressing the challenges of education in the era of globalization.